Visual representations in mathematical word problem solving among form four students in Malacca - Ahmad, Azizah; Ahmad Tarmizi, Rohani; Nawawi, Mokhtar (Elsevier, 2010)
Learning how to solve mathematical problems has been a long withstanding difficulty faced by students and has been given constant focus in mathematical development. Successful problem solvers spend more time analyzing a problem and they will find all the alternatives related to the situation. Therefore many educators (Cai, 2003, National Council of Teachers of Mathematics, 2000; Smith, 1991) agreed that teaching mathematics through problem solving hold great promise. Furthermore, according to the Malaysian Curriculum Development Centre (2003), one of the important objectives in teaching mathematics is to develop student's mathematical problem solving skills. Mathematical problems are not simply computational tasks type but are problems which also require appropriate selection of strategies and decisions that lead to logical solutions. Word problem solving is one of the important components of mathematics problem solving which incorporate real-life problems and applications. However, many researches revealed that students express great difficulties in handling a word or story problem. This study examined the use of visual representations which posed great difficulties in most mathematical tasks. Secondary students were given the 15Mathematical Processing Instrument (MPI) adapted from Hegarty and Kozhevnikov (1999). This study examined 381 students from eight secondary schools in three different districts in Malacca. Results indicated that less than two percent of the problems were solved using pictorial representation and most of the students preferred to used schematics solutions.